Changes of 1-MCP efficiency by delaying its postharvest application on 'Fuji Suprema' apples Alteração da eficiência do 1-mcp com o retardo na sua aplicação após a colheita em maçãs 'Fuji Suprema' - do Amarante C.V.T.* (2010)
It has been shown that the maximum efficiency of 1-methylcyclopropene (1-MCP) for postharvest preservation of apples is achieved when fruit are treated up to one week after harvesting. However, the full loading of commercial stores with 'Fuji' apples might take more than one week. The effects of delays for 1-MCP treatment of 'Fuji' apples have not been reported. This work was carried out to assess the effects of delaying treatment with 1-methylcyclopropene (1-MCP), after fruit harvest, on flesh firmness, titratable acidity (TA); soluble solids content (SSC), as well as on prevention of superficial scald, core browning, and decay of 'Fuji Suprema' apples. Fruit were harvested in commercial orchards of the State of Santa Catarina, located at the regions of Fraiburgo (four orchards), Bom Retiro (three orchards), and São Joaquim (three orchards), in April of 2006. Fruits were cold stored 12h after harvesting, and left during nine months in air at 0.5 ± 0.5 oC and 90-95% RH. Fruit were treated with air (control) or 1-MCP (1 μL.L-1, for 24 h), in hermetical chambers, at harvest, or after 4, 8, 12, 16, or 20 days at 0.5°C. Fruit quality was assessed after removal from cold storage, followed by seven days at 23°C. The delay of 1-MCP treatment, for up to 20 days after fruit harvesting, did not reduce its efficiency to preserve flesh firmness and to prevent core browning and decay, in fruit from the three regions, as well as to preserve the SSC in fruits from Bom Retiro and São Joaquim. However, the efficiency of 1-MCP to prevent superficial scald was reduced when its application was delayed by 16 or 20 days after harvesting, especially in apples from regions with a high susceptibility to the disorder (Fraiburgo and São Joaquim). The benefits of 1-MCP to preserve the TA were reduced in fruit from Bom Retiro, treated 20 days after harvest. These results show the benefits of 1-MCP to preserve fruit quality of 'Fuji Suprema' during long term storage in air, and the loss of its efficiency to prevent superficial scald with delays of fruit treatment superior to 12 days after harvesting.